Serum carnitine as a biomarker of sarcopenia and nutritional status in preoperative gastrointestinal cancer patients. Issue 1 (22nd December 2021) - Takagi, Akihiko; Hawke, Philip; Tokuda, Satoshi; Toda, Takeo; Higashizono, Kazuya; Nagai, Erina; Watanabe, Masaya; Nakatani, Eiji; Kanemoto, Hideyuki; Oba, Noriyuki
Abstract: Background: Sarcopenia is an important factor in the postoperative outcome of gastrointestinal cancer patients. However, little research has been carried out on potential biomarkers of sarcopenia. Carnitine is an amino acid derivative that is stored in skeletal muscle and is essential for muscle energy metabolism. The primary purpose of this study was to investigate whether serum carnitine level is a biomarker of sarcopenia in preoperative patients with gastrointestinal cancer. The secondary purposes were (i) to examine the associations between carnitine, nutritional status, and albumin level, and (ii) to determine whether carnitine is a prognostic factor for postoperative complications. Methods: One hundred fourteen patients scheduled to undergo gastroenterological surgery between August 2016 and January 2017 were enrolled. Their mean age was 68.4 ± 10.5, and 64.9% were male. Serum carnitine fractions [total carnitine (TC), free l ‐carnitine (FC), and acylcarnitine (AC)] were measured prior to surgery. The correlation between carnitine level and a variety of clinical features was analysed, including skeletal muscle index (SMI), sarcopenia, prognostic nutritional index (PNI), and postoperative complications. Results: Tumour locations included the oesophagus ( n  = 17), stomach ( n  = 16), pancreas ( n  = 20), bile duct ( n  = 9), liver [ n  = 33; primary liver cancer ( n  = 18), liver metastasis ( n  = 15)], and colorectal region ( n  = 19). TC and FC levels varied significantly by tumour location. TC and FC showed significant positive correlations with SMI [TC ( r  = 0.295, P  = 0.0014), FC ( r  = 0.286, P  = 0.0020)] and PNI [TC ( P  = 0.0178, r  = 0.222), FC ( P  = 0.0067, r  = 0.2526)]. These levels were significantly lower in the sarcopenia group (TC, P  = 0.0124; FC, P  = 0.0243). In addition, TC and FC showed significant positive correlations with ALB level [TC ( P  = 0.038 r  = 0.19), FC ( P  = 0.016 r  = 0.23)]. When patients were divided into high ALB (≥3.5 g/dL, 96 patients) and low ALB (<3.5 g/dL, 18 patients) groups, these correlations were no longer significant, but in the low ALB group there was a tendency towards a negative relationship between ALB level and both TC and FC. No significant relationship was found between postoperative complications and carnitine level. Conclusions: This study suggests that carnitine level is a biomarker of sarcopenia and nutritional status. However, it did not find an association between carnitine level and postoperative complications.